Chemical modifications of globular proteins phototriggered by an endogenous photosensitizer - Reid, Lara Olivia (2019)
The main goal of the present work was to investigate the damages photoinduced by pterin (Ptr), an endogenous photosensitizer present in human skin under pathological conditions, on a globular protein such as ubiquitin (Ub). Particular attention has been paid on the formation of covalent adducts between Ptr and the protein that can behave as photoantigen and provoke an immune system response. Here, a multifaceted approach including UV-visible spectrophotometry, fluorescence spectroscopy, electrophoresis, size exclusion chromatography, and mass spectrometry is used to establish the Ub changes triggered by UV-A irradiation in the presence of Ptr. Under anaerobic conditions, the only reaction corresponds to the formation of a covalently bound Ptr-Ub adduct that retains the spectroscopic properties of the free photosensitizer. A more complex scheme is observed in air-equilibrated solutions with the occurrence of three different processes, that is, formation of a Ptr-Ub adduct, dimerization, and fragmentation of the protein.